2020
DOI: 10.1175/jcli-d-19-0536.1
|View full text |Cite
|
Sign up to set email alerts
|

North Atlantic Multidecadal Variability Enhancing Decadal Extratropical Extremes in Boreal Late Summer in the Early Twenty-First Century

Abstract: In the beginning of the twenty-first century, weather and climate extremes occurred more and more in extratropical summer, linked to the magnified amplitudes of quasi-stationary waves and external forcing. The study analyzes the relations between multidecadal extratropical extremes in boreal late summer and the North Atlantic (NA; 358-658N, 408W-08) multidecadal variability (NAMV) in the mid-to high latitudes. The results show that multidecadal extratropical extremes link with the intensified NAMV and the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 88 publications
(137 reference statements)
0
8
0
Order By: Relevance
“…Previous studies have suggested when the AMO is in the warm North Atlantic phase, the summer NAO tends to be in its negative phase (Folland; et al., 2009; Knight et al., 2005; Sutton & Hodson, 2005; J. Zhang et al., 2020). Here, we have investigated the possible linkage between the Atlantic SST and summer NAO after performing the 9 years low‐pass filtering (Figure 4).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have suggested when the AMO is in the warm North Atlantic phase, the summer NAO tends to be in its negative phase (Folland; et al., 2009; Knight et al., 2005; Sutton & Hodson, 2005; J. Zhang et al., 2020). Here, we have investigated the possible linkage between the Atlantic SST and summer NAO after performing the 9 years low‐pass filtering (Figure 4).…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies have suggested when the AMO is in the warm North Atlantic phase, the summer NAO tends to be in its negative phase Knight et al, 2005;Sutton & Hodson, 2005;J. Zhang et al, 2020).…”
Section: Resultsmentioning
confidence: 98%
“…Both the N‐S shift and the W‐E extending of the NA JS change with global warming, exhibiting an anomaly basic flow, which is identified to link to NA and Eurasian continent (Woollings and Blackburn, 2012; Zhang et al ., 2019a). Besides, the positive AMO since the mid‐1990s can cause SRP‐like atmospheric anomalies(Zhang et al ., 2020), and result in Eurasian summer nonuniform warming, which could have important effect on the wave patterns and KE.…”
Section: Resultsmentioning
confidence: 99%
“…A positive North Atlantic Oscillation (NAO), associated with the North Atlantic SST mode, excites a high‐latitude Rossby wave train, which modulates the Ural high, Okhotsk blocking high (Wu et al ., 2012) and a mid‐latitude Eurasian wave train via the Tibetan Plateau (Sato and Takahashi, 2006; Xin et al ., 2010; Cui et al ., 2015). Previous studies also suggested that the Atlantic Multidecadal Oscillation (AMO) could excite the Silk Road Pattern‐like responses and impact on the Eurasian nonuniform warming could increase the baroclinicity and energy conversion (Sun et al ., 2019; Zhang et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the SST anomalies have significant interdecadal climate variability, such as AMO and Pacific Decadal Oscillation, which are ascribed to the wind stress and thermocline changes of the oceans physical processes (Black et al., 2014; Guo et al., 2020; Knight et al., 2006; Z. Liu, 2012). Besides, the interdecadal variation of the SST anomaly could modulate the interannual variability of SST and the associated atmospheric anomalies (Folland et al., 2009; J. Zhang et al., 2020; L. Wang et al., 2008). This is mainly because the different phase of the interdecadal variability of SST provide different background of climatic conditions (Power et al., 1999).…”
Section: Summary and Discussionmentioning
confidence: 99%